2020
DOI: 10.1007/s40430-020-2214-9
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of entropy generation in a square cavity filled with boron-water nanofluid

Abstract: The entropy generation and natural convection in a square cavity filled with boron-water nanofluid is numerically investigated under the influence of different nanoparticle volume fractions and buoyancy forces when heated from left vertical wall and cooled from right vertical wall while horizontal walls are insulated. The results are compared with copper (Cu) and aluminum oxide (Al 2 O 3) nanoparticles generally used in the applications. Differential equations are discretized over the SIMPLE algorithm and solv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…When convection or conduction dominates, depending on the kind of flow, heat transfer is measured. In a square cavity filled with boron-water nanofluid, free convection and entropy production were measured when the left vertical wall was heated and the right vertical wall was cooled while the horizontal walls were kept apart [73]. The results were compared to those of copper (Cu) and aluminum oxide (Al2O3) nanoparticles, which are routinely used in complex enclosures with nanofluid for natural convection applications.…”
Section: Free Convection In a Classical Cavity With Nanofluidmentioning
confidence: 99%
“…When convection or conduction dominates, depending on the kind of flow, heat transfer is measured. In a square cavity filled with boron-water nanofluid, free convection and entropy production were measured when the left vertical wall was heated and the right vertical wall was cooled while the horizontal walls were kept apart [73]. The results were compared to those of copper (Cu) and aluminum oxide (Al2O3) nanoparticles, which are routinely used in complex enclosures with nanofluid for natural convection applications.…”
Section: Free Convection In a Classical Cavity With Nanofluidmentioning
confidence: 99%
“…Therefore, several numerical pieces of research attending to interpret entropy production and free convection of nano- and hybrid nano- fluids in closed cavities have been done. A numeral study of heat transfer and entropy generation of boron-water nanofluid in a square cavity was performed by (Şahin, 2020). It was concluded that an increase in Rayleigh number leads always to an increase in the entropy produced whatever the type of nanofluid.…”
Section: Introductionmentioning
confidence: 99%
“…Gallavotti [13] has computed stationary states of nonequilibrium in a point of view. Additionally, Kurnia et al [14] have studied the cooling of microchannel with heat transfer performance on entropy production, and Şahin [15] has numerically explored entropy generation in a square cavity filled with boron-water nanofluid. Moreover, Soltanipour et al [16] have numerically examined ferrofluid forced convection with magnetic field and entropy generation in a curved pipe.…”
Section: Introductionmentioning
confidence: 99%